Inventory models for deteriorating items with power pattern demand rate / Adaraniwon Amos Olalekan - Adaraniwon Amos , Olalekan (2020)
Inventory management has become a prevalent topic in the field of operational research over some decades now. It cuts across many areas like management sciences, statistics and engineering. However, research focusing on inventory model with power demand pattern is quite limited. Demand patterns are defined as different ways by which products are removed out of inventory to supply customers demand during the schedule period. Power demand pattern permits suiting the demand to a more practical situation. In this research, four deterministic inventory model for deteriorating items with power demand pattern has been developed. We considered in the first models an inventory model for deteriorating item with power demand pattern and time-dependent holding cost without shortages, in the second model, we considered an inventory model for linear time-dependent deteriorating rate and time-varying demand with shortages completely backlogged, while in the third model, an inventory model for delayed deteriorating items with power demand considering shortages and lost sales. Linear deteriorating inventory policy for products with power demand pattern and variable holding cost considering shortages is developed in the final model with some additional features. In all the models, the objective is to determine the optimal replenishment strategy for the proposed inventory model to minimise the total inventory cost per unit time. Mathematical formulation for and analysis of the inventory problems were developed within the framework of the model assumptions. A system of differential equations incorporating initial and boundary conditions are given for the proposed inventory policy, and the problem solved using Microsoft@Excel@ Solver and maple software 2018 to obtain the optimal solutions for all the models. Numerical examples are given at the end of each developed inventory model to establish the robustness and effectiveness of the models. Moreover, the sensitivity analysis of each model was carried out to see the effects of various changes in some possible parameters combination of the inventory policy.